Implementation of civil law in resolving inheritance disputes in Banten province - Aris Setyanto Pramono; Safiulloh Safiulloh; Ainun Nuraini (Institute Of computer Science (IOCS), 2026)
This study aims to analyze the implementation of civil law in resolving inheritance disputes in Banten Province. Inheritance disputes are a common legal problem in society due to differences in understanding regarding the distribution of inheritance, weak administration of property ownership, and conflicts of interest between heirs. These conditions give rise to disputes that can disrupt family relationships and social stability. This study uses a qualitative research method with an empirical juridical approach. Data were obtained through observation, interviews, documentation, and literature studies related to civil law and inheritance dispute resolution. Data analysis was conducted descriptively to describe the implementation of civil law in the practice of inheritance dispute resolution in Banten society. The results of the study indicate that the implementation of civil law in resolving inheritance disputes in Banten Province has not been running optimally. Contributing factors include the community's low understanding of inheritance law provisions, the strong influence of local customs and culture, and a lack of public awareness in preparing legal documents such as wills and ownership deeds. Inheritance dispute resolution is generally carried out through family deliberations, mediation, and court channels if the conflict cannot be resolved amicably. The role of government officials, community leaders, and judicial institutions is crucial in providing legal education and ensuring legal certainty for disputing parties. This research is expected to contribute to the development of civil law studies and provide input for the government and community in creating fair, effective, and legally certain inheritance dispute resolution.